Analisis Faktor-Faktor yang Mempengaruhi Level Internet Addiction Disorder pada Siswa SMA Negeri 42 Jakarta - Zuhana Realita Alfy (SAP (Susunan Artikel Pendidikan), 2019)
In addition to providing convenience in all fields, the internet also has a negative impact. Internet Addiction Disorder refers to the pattern of excessive internet usage and disrupts the lives of internet users themselves. This research was shown to determine the level of Internet Addiction Disorder in Jakarta 42 Senior High School students along with their characteristics and factors that influence the level of the Internet Addiction Disorder. The analysis used was descriptive analysis and multinomial logistic regression analysis. The results of this research indicate that the majority of Jakarta State High School 42 students suffer from Internet Addiction Disorder at the Moderate level. There are factors that influence the level of Internet Addiction Disorder, namely the motive for using the internet, the length of time being a user, the quality of relationships with friends, and the income of peers parents greatly influencing adolescent behavior including behavior in internet usage